2012
DOI: 10.1002/jor.22145
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term administration of AMD3100, an antagonist of SDF‐1/CXCR4 signaling, alters fracture repair

Abstract: Fracture healing involves rapid stem and progenitor cell migration, homing, and differentiation. SDF-1 (CXCL12) is considered a master regulator of CXCR4-positive stem and progenitor cell trafficking to sites of ischemic (hypoxic) injury and regulates their subsequent differentiation into mature reparative cells. In this study, we investigated the role of SDF-1/CXCR4 signaling in fracture healing where vascular disruption results in hypoxia and SDF-1 expression. Mice were injected with AMD3100, a CXCR4 antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 47 publications
1
83
0
Order By: Relevance
“…S4), which may mediate the migration of potentially regenerative stem cells into tissues (40). This result may be particularly important given that the inhibition of CXCL12 or corresponding C-X-C chemokine receptor type 4 was recently reported to delay bone fracture repair (41). Similarly, the parallel up-regulation of the C-X3-C chemokine motif ligand 1 observed after CCL22 microparticle treatment (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…S4), which may mediate the migration of potentially regenerative stem cells into tissues (40). This result may be particularly important given that the inhibition of CXCL12 or corresponding C-X-C chemokine receptor type 4 was recently reported to delay bone fracture repair (41). Similarly, the parallel up-regulation of the C-X3-C chemokine motif ligand 1 observed after CCL22 microparticle treatment (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…59 In a murine model of fracture healing, we identified CXCL12 expression in the fracture callus in hypertrophic cartilage and immature cartilage close to pre-existing cortical bone. 66 Furthermore, CXCL12 staining colocalized with staining for Hypoxyprobe (pimonidazole hydrochloride; Hypoxyprobe, Inc., Burlington, MA, USA) a marker of hypoxic cells. 66 Almost all cells in the callus, including chondrocytes, osteoblasts, osteoclasts and undifferentiated mesenchymal Homing mechanisms in fracture repair C Yellowley tissue cells, stained positively for CXCR4.…”
Section: Cxcl12 and Bone Regenerationmentioning
confidence: 96%
“…Specific chemokine receptors (e.g., CCR1, CCR7, CCR9, CXCR4, CXCR5, and CXCR6) are important mediators in this matter, and among them CXCR4 and its ligand (CXCL12 or stromal-derived factor 1; SDF1) are the most widely investigated mediators in the MSC recruitment process [Kitaori et al, 2009]. A localized hypoxic condition occurs in the initial stage of fracture due to vascular damage that acts as a useful recruitment factor and regulatory stimulus for MSCs and other progenitor cells [Mehta et al, 2012;Toupadakis et al, 2012]. It has also been suggested that new bone formation occurs under hypoxic conditions [Olmsted-Davis et al, 2007].…”
Section: Msc Homing and Recruitment To Bone Defectsmentioning
confidence: 99%